2016
DOI: 10.1002/chem.201601326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Headgroups on Small‐Ion Permeability across Archaea‐Inspired Tetraether Lipid Membranes

Abstract: This paper examines the effects of four different polar headgroups on small-ion membrane permeability from liposomes comprised of Archaea-inspired glycerolmonoalkyl glycerol tetraether (GMGT) lipids. We found that the membrane-leakage rate across GMGT lipid membranes varied by a factor of ≤1.6 as a function of headgroup structure. However, the leakage rates of small ions across membranes comprised of commercial bilayer-forming 1-palmitoyl-2-oleoyl-sn-glycerol (PO) lipids varied by as much as 32-fold within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…According to these data, a higher proportion of tetraether lipids over diether lipids in archaeal membranes represents a clear lipid adaptation to elevated temperatures. Although a tetraether structure itself confers low ion permeability to the membrane ( Koyanagi et al, 2016 ), the modifications of archaeal tetraether structures revealed by our study (e.g., H-shape, additional methylation or cyclopentane rings) suggest further requirements for avoiding futile ion cycling or ion leakage in high-temperature environments.…”
Section: Discussionmentioning
confidence: 80%
“…According to these data, a higher proportion of tetraether lipids over diether lipids in archaeal membranes represents a clear lipid adaptation to elevated temperatures. Although a tetraether structure itself confers low ion permeability to the membrane ( Koyanagi et al, 2016 ), the modifications of archaeal tetraether structures revealed by our study (e.g., H-shape, additional methylation or cyclopentane rings) suggest further requirements for avoiding futile ion cycling or ion leakage in high-temperature environments.…”
Section: Discussionmentioning
confidence: 80%
“…Using a previously described pH equilibration method to estimate initial rates of leakage of small ions (e.g., H + , OH − , Na + , Cl − , and other buffer ions) from liposomes, we first evaluated the observed initial rate of small ion membrane leakage to study whether the addition of free cholesterol (40 mol %) to 1‐palmitoyl‐2‐oleoyl‐phosphatidylcholine (POPC), GMGTPC‐CH, or GcGTPC‐CH liposomal formulations affected membrane permeation of small ions (see Figure S4 in the Supporting Information). As expected, the addition of cholesterol to POPC resulted in a ten‐fold decrease in small ion membrane leakage compared to cholesterol‐free POPC membranes (Figure A).…”
Section: Figurementioning
confidence: 99%
“…This result was in agreement with previousr eports, which showed that adding4 0-50 mol %o ff ree cholesterol to diacyl lipids [25] maintains af luid phase and diminishes its phase transition. Furthermore, liposomes remained structurally stable throughout the time frame of leakage experiments andw edid not observe Using ap reviously described pH equilibrationm ethodt oe stimate initial rates of leakageo fs mall ions (e.g.,H + ,O H À ,N a + , Cl À ,a nd other buffer ions) from liposomes, [18,26] we first evaluated the observed initial rate of small ion membrane leakage to study whether the addition of free cholesterol (40 mol %) to 1-palmitoyl-2-oleoyl-phosphatidylcholine (POPC), GMGTPC-CH, or GcGTPC-CH liposomal formulations affectedm embrane permeationo fs malli ons (see Figure S4 in the Supporting Information). Furthermore, liposomes remained structurally stable throughout the time frame of leakage experiments andw edid not observe Using ap reviously described pH equilibrationm ethodt oe stimate initial rates of leakageo fs mall ions (e.g.,H + ,O H À ,N a + , Cl À ,a nd other buffer ions) from liposomes, [18,26] we first evaluated the observed initial rate of small ion membrane leakage to study whether the addition of free cholesterol (40 mol %) to 1-palmitoyl-2-oleoyl-phosphatidylcholine (POPC), GMGTPC-CH, or GcGTPC-CH liposomal formulations affectedm embrane permeationo fs malli ons (see Figure S4 in the Supporting Information).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Kakinuma and coworkers previously reported the total synthesis of a natural archaeal 72-membered macrocyclic tetraether lipid, 16 only a few groups have reported syntheses of archaea-like tetraether lipids that incorporate structural features found in natural lipids such as: ether glycerol linkages, tethering of lipid tails, and the incorporation of small rings within the transmembrane portion of the lipid. [17][18][19][20][21][22] Among the few reported examples of synthetic archaea-like lipids, only Benvegnu and coworkers have shown that synthetic tetraether lipids could be used for the delivery of genes to cells. 23,24 To the best of our knowledge, however, the evaluation of encapsulation and permeability of small molecules from tetraether lipids has been limited to model fluorophores (e.g., carboxyfluorescein) 19,25,26 and small ions (e.g., H + , OH − , Na + , Cl).…”
mentioning
confidence: 99%